Numerals in early Greek New Testament manuscripts : text-critical, scribal, and theological studies - Cole, Zachary J. (New Testament Tools, Studies and Documents, 2017)
In Numerals in Early Greek New Testament Manuscripts , Zachary J. Cole provides the first in-depth examination of the seemingly obscure, yet important topic: how early Christian scribes wrote numbers and why. While scholars have long been aware that Christian scribes occasionally used numerical abbreviations in their books, few have been able to make much sense of it. This detailed analysis of numerals in manuscripts up through the fifth century CE uncovers a wealth of palaeographical and codicological data. Among other findings, Zachary J. Cole shows that some numerals can function as "visual links" between witnesses, that numbers sometimes-though rarely-functioned like nomina sacra , and that Christians uniquely adapted their numbering system to suit the needs of public reading.